MICROBIOLOGICAL QUALITY OF SOME ICED. FISHES OF IMPHAL MARKET, MANIPUR - LILABATI, H.; VISHWANATH, W. (Journal of Indian Fisheries Association, 2015)
Imphal is the main marketing centre. of fish in Manipur. As fishproduction of the state. is not sufficient to meet the demands, about120 metric tons of iced fishes are annually brought from other statesand sold in this market. Microbiological quality of iced Wallago attu,~abeo rohita; L. gonius and Aorichthys aor in respect of total fungalcount (TFC), total plate Â·count of bacteria (TPC), Most Probable Number(MPN) of coliforms, Streptococci, Staphylococcus, Salmonella andEscherichia coli in four tissues viz~ skin, muscle, gill and intestinewere analysed. In all cases, the counts were highest in the gills andlowest in the muscles. 'rhe values of TFC, TPC, coliforms, Streptococciand Staphylococci were Oa103/g 106-108/g, 2-a/g, 10-105/g, 10-105/grespectively. E. coli and Salmonella were not detected in any of thesamples while. the ice used in the preservation contained 105â€¢ 107 ofTPC per gram. The microbiological quality of the iced fishes of Imphalmarket were .adjudged poor. The extremely high counts of bacteriamight be due to (1) poor. quality ~nd left over fishes being packed, (2)cont~ct with contaminated ice .and (3) repeated thawing and freezingduring. the process of marketing and transportation.